2015
DOI: 10.1039/c5nr04879f
|View full text |Cite
|
Sign up to set email alerts
|

Engineering excitonic dynamics and environmental stability of post-transition metal chalcogenides by pyridine functionalization technique

Abstract: Owing to their strong photon emission, low excitonic binding energies, and nearly-ideal band offset values for water splitting reactions, direct gap quasi-2D gallium chalcogenides are potential candidates for applications in energy harvesting, optoelectronics, and photonics. Unlike other 2D materials systems, chemical functionalization of gallium chalcogenides is still at its seminal stages. Here, we propose vapor phase pyridine intercalation technique to manipulate optical properties of gallium chalcogenides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…[11][12][13][14][15][16] Due to the fact that PTMCs possess a suitable bandgap for photovoltaics and transistors, [4][5][6][7][17][18][19][20][21][22] excellent thermal transport, 21,23 inherent flexibility, [24][25][26] and smaller exciton binding energies [4][5][6] make them viable substitutes for TMDs in device applications. In addition, it has been reported that applying strain, 24,26,27 creating heterostructures, [28][29][30][31] and chemical functionalization [32][33][34] can effectively tune the electronic and optical properties of monolayer GaSe, and it has been reported that GaSe can be used as a suitable substrate for other 2D materials. 35,36 Although GaSe has been reliably synthesized and the lattice constant, quasiparticle gap, and optical gap have been experimentally characterized, 23,[37][38][39][40][41][42][43][44] results obtained...…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Due to the fact that PTMCs possess a suitable bandgap for photovoltaics and transistors, [4][5][6][7][17][18][19][20][21][22] excellent thermal transport, 21,23 inherent flexibility, [24][25][26] and smaller exciton binding energies [4][5][6] make them viable substitutes for TMDs in device applications. In addition, it has been reported that applying strain, 24,26,27 creating heterostructures, [28][29][30][31] and chemical functionalization [32][33][34] can effectively tune the electronic and optical properties of monolayer GaSe, and it has been reported that GaSe can be used as a suitable substrate for other 2D materials. 35,36 Although GaSe has been reliably synthesized and the lattice constant, quasiparticle gap, and optical gap have been experimentally characterized, 23,[37][38][39][40][41][42][43][44] results obtained...…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that PTMCs possess a suitable band gap for photovoltaics and transistors [4][5][6][7][17][18][19][20][21][22] , excellent thermal transport 21,23 , inherent flexibility [24][25][26] and smaller exciton binding energies [4][5][6] make them viable substitutes for TMDs in device applications. In addition, it has been reported that applying strain 24,26,27 , creating heterostructures [28][29][30][31] and chemical functionalization [32][33][34] can effectively tune the electronic and optical properties of monolayer GaSe and it has been reported that GaSe can be used as a suitable substrate for other 2D materials 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the attention of material science and condensed matter physics has been widened towards new single layer structures such as silicene 4,5 , germanene [5][6][7] , transition-metal dichalcogenides (TMDs) [8][9][10][11] , alkaline-earth-metal hydroxide (AEMHs) 12 and post-transition metal chalcogenides (PTMCs). [13][14][15] These individual monolayers posses various significant electronic and optical properties which make them promising candidates for the next generation of nanoscale devices. [16][17][18] For instance, monolayer TMDs are direct band gap semiconductors unlike their bulk counterparts, [9][10][11] and exhibit large exciton binding energies in the order of 0.1-1.0 eV which results in exciton resonances at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…12 Similar to Ca(OH) 2 , monolayer GaS and GaSe have been synthesized recently and it has been shown that both monolayers are indirect gap semiconductors and they are suitable candidates for use in field-effect transistors and nanophotonic devices. 14,[26][27][28] Another important aspect of the mentioned layered structures is their usage as building blocks for novel multi-layer heterostructures. Recently, a new field of research in materials science has emerged that deals with the stacking of two or more different monolayers on top of each other, namely van der Waals (vdW) heterostructures.…”
Section: Introductionmentioning
confidence: 99%